A framework for automatic verification of programing exercises - Quan, T.T.; Nguyen, P.H.; Bui, T.H.; Huynh, L.V.; Do, A.T. (2009 2nd IEEE International Conference on Computer Science and Information Technology, 2009)
Programming skill is crucial for all Computer Science students which can only be mastered through intensive exercise practice. Apart from traditional face-to-face manner of teaching programming, with the recent advancement of Internet and advanced program verification techniques, Web-based tutoring systems that can play the role of teacher are increasingly considered. In this paper, we suggest a framework for automatic verification of program exercises without risking the execution of actual code. In our framework, we first employ theorem proving to verify programming exercises and model checking to generate counter-examples to the learners. Our framework is being implemented and employed in a real education university environment with some initial promising results.